IMPROVING STUDENTSâ VOCABULARY MASTERY BY USING FLASH CARD AT FORTH GRADE STUDENTS IN SDN LAWANGAN DAYA 2 PAMEKASAN - Setiyawan, Arisandi (WACANA DIDAKTIKA, 2015)
From the preliminary research of the fourth graders of SDN Lawangan Daya 2Pamekasan, it showed that most of the students had a lack of vocabulary mastery. ThisÂ research is conducted to find an effective and appropriate strategy to improve studentsâÂ vocabulary mastery by using flashcard. Therefore, the appropriate design for this researchÂ is Classroom Action Research (CAR). The researcher implemented the strategy in oneÂ cycle, those are: planning, implementing, observing and reflecting. The result of the classÂ vocabulay test is analyzed quantitatively, while the result of the data achieved fromÂ observation class is analyzed qualitatively. The finding shows that the studentsâÂ vocabulary mastery increase significantly from the preliminary research. The result can beÂ concluded that (1) teaching and learning process needs an appropriate and effecctiveÂ strategy, (2) flashcard is considered as an appropriate technique to improve the studentsâÂ vocabulary mastery.